Anchoring of SiC whiskers on the hollow carbon microspheres inducing interfacial polarization to promote electromagnetic wave attenuation capability. (30th April 2021) - Chen, Jing-Peng; Du, Yi-Feng; Wang, Zhe-Fan; Liang, Lei-Lei; Jia, Hui; Liu, Zhuo; Xie, Li-Jing; Zhang, Shou-Chun; Chen, Cheng-Meng
Abstract: The SiC whiskers/hollow carbon microspheres (SiCw/HCMS) were successfully synthesized by a combination of the spray drying technology and the carbothermal reduction method. The anchoring of SiCw on HCMS shells improves the thermostability of composites and induces the formation of new heterointerfaces between SiC whiskers and HCMS. Experimental characterizations together with DFT calculations show that compared to intrinsic defects and functional groups in SiCw/HCMS, the formed heterointerfaces trigger the separation of positive and negative charges and induce large dipole moments, resulting in the intensive dielectric polarization loss. Consequently, SiCw/HCMS samples achieve an excellent electromagnetic wave absorption, where the reflection loss value of SiCw/HCMS-1450 reaches to −48.60 dB at 8.0 GHz with a thickness of 2.6 mm and the maximum effective absorbing bandwidth is 4.34 GHz. This work investigates a deep insight into the relationship between interfacial polarization loss and the electromagnetic wave attenuation and designs a novel absorbent that exhibits great potential for electromagnetic wave absorption at high-temperature environments. Graphical abstract: SiC whiskers/hollow carbon microspheres (SiCw/HCMS) were successfully designed and synthesized by spray drying technology and carbothermal reduction method. Benefiting for designed structure, the heterointerfaces between SiC whiskers and HCMS induce the separation of positive and negative charges and result in large dipole moment, contributing to a significant polarization loss. SiCw/HCMS samples exhibit a superior electromagnetic wave absorption performance. Image 1 Highlights: SiCw/HCMS were synthesized by a combination of the spray drying technology and the carbothermal reduction method. The heterointerfaces induce a large polarization loss than that of defective structures in SiCw/HCMS samples. RL value of SiCw/HCMS-1450 reaches −48.60 dB at 8.0 GHz with a thickness of 2.6 mm and the EAB is 4.34 GHz.